Unpacking Self-Directed Learning Readiness: A Mapping and Analysis of Measurement Scales - Piratheeban, K.; Bandara, L.M.K. (University of Colombo, 2025)
This study aims to map and analyse the measurement scales used to assess SelfDirected Learning Readiness (SDLR). With self-directed learning (SDL) emerging as a critical competency for personal and professional development, a comprehensive evaluation of the scales designed to measure SDLR is essential. The Web of Science database was selected as the source for this systematic literature review, spanning 35 years from 1989 to 2023, with 97 articles identified. After applying seven exclusion criteria, 59 articles were selected for final analysis. The study catalogues and evaluates 13 instruments used to assess SDLR, focusing on their dimensions, attributes, and historical development. The findings reveal that the Self-Directed Learning Readiness Scale for Nursing Education and the Self-Rating Scale of Self-Directed Learning are the most frequently utilized and cited tools. A continental analysis shows that SDLR research is primarily concentrated in North America and Asia, with significant contributions from the USA (16.67%) and Taiwan (10%). In contrast, the research from developing regions remains limited. The study also identifies 64 SDLR dimensions across the 13 tools, resulting in 52 distinct dimensions. Further, the research classifies these dimensions into eight categorical dimensions: Motivation, Collaborative Learning Activities, Knowledge construction, Self-Efficacy, Self-Management, SelfReflection and Evaluation, Autonomy, and Planning, offering a structured framework for assessing SDLR. The limited exploration of SDLR measurement in non-medical fields, especially at the school level, highlights the need for contextually and developmentally appropriate tools for younger learners. This study provides valuable insights for future research and developing comprehensive SDLR assessment tools in diverse educational settings.
Keywords: Self-Directed Learning Readiness; Self-directed Learning Competency; Learning Autonomy; Lifelong learning; Self-directed Learner